Food supplements and their effectiveness in muscle hypertrophy (Research, Society and Development, 2022)
Objective: to carry out a bibliographic research on the effectiveness of food supplements in muscle hypertrophy. Methodology: refers to an integrative review of the observational quantitative literature. The search for articles was carried out in the VHL, Scielo, Lilacs, PubMED and Google Scholar databases between August 2021 and May 2022. 72 articles were found and only 11 were selected for discussion of the results. The descriptors used were: “Hypertrophy”, “Bodybuilding”, “Food supplements”. The inclusion criteria were: original articles indexed in the selected databases, in Portuguese and English; published between 2017 and 2022. Exclusion criteria were publications of diploma theses, conference materials, etc., dissertations, monographs and articles unrelated to the topic. Results: it was found among the most used supplements is whey protein, as it was possible to show that it provides muscle mass gain, increased strength and muscle hypertrophy. When consumed by elderly women who practice resistance training, it prevents sarcopenia and dynapenia. As for creatine when combined with strength and resistance training, it results in increased strength as well as aids in muscle hypertrophy. As for supplements such as collagen, carbohydrates and vitamin D3, they are capable of promoting better results in strength and resistance training and especially if used together with other supplements. Final considerations: more studies should be developed demonstrating the importance of discussing the subject, as well as the effectiveness of food supplements for muscle hypertrophy.